2008
DOI: 10.1210/en.2008-1003
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Receptor Is Required for Normal Glucose Homeostasis and Modulation of β-Cell Mass during Pregnancy

Abstract: Increased islet mass is an adaptive mechanism that occurs to combat insulin resistance during pregnancy. Prolactin (PRL) can enhance beta-cell proliferation and insulin secretion in vitro, yet whether it is PRL or other pregnancy-related factors that mediate these adaptive changes during pregnancy is unknown. The objective of this study was to determine whether prolactin receptor (Prlr) is required for normal maternal glucose homeostasis during pregnancy. An ip glucose tolerance test was performed on timed-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
296
2
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(327 citation statements)
references
References 29 publications
22
296
2
7
Order By: Relevance
“…Recent reports have demonstrated that prolactin enhanced human b-cell viability (Yamamoto et al 2008) as well as b-cell proliferation through the PI3K signaling pathway (Hü gl & Merger 2007). During pregnancy, both pancreatic b cells and islet endothelial cell display a highly reproducible physiological proliferation that requires the expression of prolactin receptor (Huang et al 2009). From all these observations, reduction of prolactin levels by glucose is important to consider for both islet and endothelial cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have demonstrated that prolactin enhanced human b-cell viability (Yamamoto et al 2008) as well as b-cell proliferation through the PI3K signaling pathway (Hü gl & Merger 2007). During pregnancy, both pancreatic b cells and islet endothelial cell display a highly reproducible physiological proliferation that requires the expression of prolactin receptor (Huang et al 2009). From all these observations, reduction of prolactin levels by glucose is important to consider for both islet and endothelial cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…While liver predominantly expresses the short isoform, pancreatic beta cells primarily utilise the long variant of the receptor. Of all tissues examined, expression of PRLRs on rodent beta cells is among the highest and PLs are known to be an important signal for the altered regulation of glucose homeostasis during pregnancy [10,11]. However, a number of interspecies differences exist and these may contribute to the wide variation in reproductive and growth patterns seen between different mammalian families.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical models have demonstrated that prolactin and placentally derived HPL both bind to the prolactin receptor on the b-cells and induce a series of downstream intracellular mediators that ultimately stimulate b-cell growth and proliferation (8)(9)(10)(11). Indeed, the prolactin receptor has been shown to be essential for the expansion of b-cell mass in pregnancy (12,13). Whereas prolactin and HPL are key determinants of this normal physiologic response, the furan fatty acid metabolite 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid (CMPF) was recently identified as a negative regulator of insulin secretion and hence a mediator of b-cell dysfunction in GDM (14,15).…”
mentioning
confidence: 99%